Las reformas al reglamento general de la Ley Orgánica de Servicio Público y sus consecuencias jurídicas en la Dirección Distrital del Mies Bolívar 2021. - Báez Aguilar, Sonia Soledad (2023)
The present investigation focused on analyzing the figure of definitive cessation of functions, taking into consideration the provisions of the Organic Law of Public Service, and the provisions contained in the General Regulations of the Organic Law of Public Service, where reference is made to the cessation of functions due to the purchase of resignations with compensation, in order to be able to establish the legal consequences that were generated for the public servants who were separated from the District Directorate of the Ministry of Economic and Social Inclusion of Bolívar until the year 2021. The problem of the subject under study, lies in the violation of the right to work in correlation with other rights protected in the supreme letter of the Ecuadorian Legislation, all this product of the Reform to the General Regulation of the Organic Law of Public Service, to the included by executive decree 813 contained in the Supplement to the Official Gazette 489, 12-VII-2011, the cessation of functions due to the purchase of mandatory resignation with compensation, which affected the job stability of public servants. For the development of the present investigation, a type of mixed investigation was used, that is, the qualitative and quantitative method was applied. The level of the research is descriptive and correlational. The research methodology used is descriptive and experimental. Finally, regarding the research technique, the survey and the survey sheet instrument were used, which was applied to the most suitable population, that is, to legal professionals from Guaranda Canton, Bolívar Province, experts in the field. administrative and labor Regarding the expected results, it has been possible to demonstrate that incidents and repercussions have been generated for workers since the General Regulation of the Organic Law of Public Service was reformed by executive decree 813, since public servants who worked in the District Directorate of Ministry of Economic and Social Inclusion were dismissed from their functions for the purchase of mandatory resignations with compensation. Keywords: public administration, cessation of functions, purchase of resignations, compensation, public servants.